Development and Psychometric Validation of the Lincoln Canine Anxiety Scale - Mills, Daniel S.; Mueller, Hanns Walter; McPeake, Kevin; Engel, Odilo (Frontiers in Veterinary Science, 2020)
Anxiety in dogs, especially in relation to certain noises, is a common issue which can lead to clinically significant problems like noise phobias. While several scales have been used to assess sound sensitivity and reactivity, clinical monitoring has tended to depend on unvalidated methods, general assessment and/or historical comparison with owners’ recall of previous episodes. Therefore we aimed to develop and validate a scale to assess canine anxiety. Materials and Methods: We used the data from 226 dogs from a previously reported double blind placebo controlled study in order to determine the validity of the 16 item “Lincoln Canine Anxiety Scale”. Unidimensionality was assessed through correlation between individual item scores and total score, with internal consistency assessed using Cronbach´s alpha. Factor analysis was used to determine the dimensionality of the scale. Item response theory (IRT) was used to gain insight into the value of single items to the overall scale scores. To characterize the score characteristics in an anxiety-eliciting context we analyzed the behaviours of placebo treated dogs assessed at 00:20h, the time point of maximum noise stimulus during New Year’s Eve fireworks. Sensitivity of the scale to treatment effects was determined from its performance in the wider study. Results: The majority of correlations between individual items and total score were greater than 0.48, with Cronbach´s alpha equalling 0.88, indicating good internal consistency. Principal Component Analysis (PCA) confirmed a unidimensional structure. IRT indicated that the scale could be reduced to 11 items without significantly reducing its value. The scale showed good treatment and stimulus sensitivity, with a score change of approximately 20 points differentiating “no/worse” effect from an “excellent” effect and a 30 % difference between treatment (imepitoin) and placebo. Conclusion: In our initial validation of the Lincoln Canine Anxiety Scale appears to provide a reliable method for determining anxiety and fear responses by dogs and monitoring the effects of treatment.